Care Coordination Can Reduce Unmet Needs of Persons With Severe and Persistent Mental Illness - Isaacs, Anton; Beauchamp, Alison; Sutton, Keith; Kocaali, Nilay (Frontiers in Psychiatry, 2019)
Introduction: Persons with severe and persistent mental illness [SPMI] have multiple and complex needs, many of which are not health related. Mental health services are unable to address these needs without collaboration with other agencies. In the absence of this collaboration, persons with SPMI often fall through the system cracks and are unlikely to experience recovery. Furthermore, previous studies have shown that unmet accommodation needs are associated with unmet needs in other areas. This study aimed to ascertain whether a care coordination model adopted in Australia’s Partners in Recovery [PIR] initiative was able to reduce unmet needs in such persons and also if meeting accommodation needs were associated with meeting other needs. Methods: This was a longitudinal study where met and unmet needs of clients measured using the Camberwell Assessment of Needs Short Appraisal Schedule [CANSAS] were compared at enrolment and exit from the PIR initiative. Logistic regression was used to examine the association between change in accommodation needs and change in other CANSAS variables. Results: In total, 337 clients (66% of 508 clients) had both baseline and follow-up data, and were seen within the time frame of 14 to 101 weeks. At baseline, the most frequently reported unmet needs were psychological distress, daytime activity, and company (89%, 72% & 67% respectively). At follow-up, these had decreased to 27%, 22% & 22%, respectively. The proportions of clients with an unmet need at baseline who subsequently progressed to having that need met at follow-up ranged between 62% and over 90%. Change in accommodation needs from unmet to met was associated with changes in monetary needs and needs related to childcare, food, safety to self, education and access to other services with the greatest change seen for monetary needs (adjusted OR 2.87, 95%CI 1.76, 4.69). Conclusions: Reducing needs of persons with severe and persistent mental illness is the starting point of recovery and is a good indicator of psychiatric care. Care coordination is a useful way to address multiple and complex needs of persons with SPMI. While addressing needs, priority must be given to meeting accommodation needs.